Open-source distributed learning validation for a larynx cancer survival model following radiotherapy. (August 2022) - Hansen, Christian Rønn; Price, Gareth; Field, Matthew; Sarup, Nis; Zukauskaite, Ruta; Johansen, Jørgen; Eriksen, Jesper Grau; Aly, Farhannah; McPartlin, Andrew; Holloway, Lois; Thwaites, David; Brink, Carsten
Highlights: Open-source distributed learning can validate survival models without sharing patient-sensitive data. The MAASTRO model can predict the survival of larynx cancer patients treated at Odense and The Christie. The absolute survival prediction requires a recalibration factor of 0.78 to predict survival accurately. The baseline hazard between the two institutions is significantly different. Additional parameters are needed to improve survival prediction. Abstract: Introduction: Prediction models are useful to design personalised treatment. However, safe and effective implementation relies on external validation. Retrospective data are available in many institutions, but sharing between institutions can be challenging due to patient data sensitivity and governance or legal barriers. This study validates a larynx cancer survival model performed using distributed learning without any sensitive data leaving the institution. Methods: Open-source distributed learning software based on a stratified Cox proportional hazard model was developed and used to validate the Egelmeer et al. MAASTRO survival model across two hospitals in two countries. The validation optimised a single scaling parameter multiplied by the original predicted prognostic index. All analyses and figures were based on the distributed system, ensuring no information leakage from the individual centres. All applied software is provided as freeware to facilitate distributed learning in other institutions. Results: 1745 patients received radiotherapy for larynx cancer in the two centres from Jan 2005 to Dec 2018. Limiting to a maximum of one missing value in the parameters of the survival model reduced the cohort to 1095 patients. The Harrell C-index was 0.74 (CI95%, 0.71–0.76) and 0.70 (0.66–0.75) for the two centres. However, the model needed a scaling update. In addition, it was found that survival predictions of patients undergoing hypofractionation were less precise. Conclusion: Open-source distributed learning software was able to validate, and suggest a minor update to the original survival model without central access to patient sensitive information. Even without the update, the original MAASTRO survival model of Egelmeer et al. performed reasonably well, providing similar results in this validation as in its original validation